MicroRNAs and Related Cytokine Factors Quickly Respond in the Immune Response of Channel Catfish to Lipopolysaccharides and β‐Glucan Stimulation. Issue 4 (21st September 2021) - Tang, Xuelian; Fu, Jinghua; Shi, Yifu; Guan, Wanting; Xu, Minjun
Abstract: MicroRNAs (miRNAs) are well‐known as powerful regulators of gene expression, with their potential to serve for immunology widely researched in mammals and birds but rarely in fishes. To better understand fish immunology behavior, we herein investigated nine immune‐related miRNAs that were reported in other animals, as well as five related cytokine factors and lysozyme (LZM) in the liver, anterior kidney, and spleen of Channel Catfish Ictalurus punctatus after being stimulated by lipopolysaccharides (LPS) and β‐glucan. We also predicated the potential targets of these miRNAs via bioinformatics and further investigated nine of them via quantitative real‐time PCR. Results showed that expressions of the nine miRNAs were quickly changed in varying extent after stimulation by LPS, especially for miR‐122, miR‐142a, miR‐155, and miR‐223, which were significantly changed in spleen, and the same occurred for the LZM and three cytokine factors TNF‐α, IFN‐γ and TLR2. Compared with LPS, although most of the miRNAs and the cytokine genes were also affected by β‐glucan, the extent of the effect was weak. Bioinformatics analysis revealed many immune‐related targets of the miRNAs, with some of them reported by previous studies. For the nine investigated target genes, seven targets (77.8%) were significantly upregulated after the stimulation of LPS. It therefore can be inferred that the immune‐related miRNAs, LZM, and cytokine factors elicited quick immune responses of Channel Catfish to LPS stimulation as in other animals, but the regulation mechanism of miRNAs might be complex and diverse. This research will contribute to a better understanding will support further immunology research in fishes.